1971
DOI: 10.1111/j.1365-2222.1971.tb00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E antibodies to milk proteins

Abstract: Ninety-eight sera of normal and hospitalized infants were tested for IgE antibodies against milk antigens. These antibodies were detected by the radioimmunodiffusion (RID) technique using rabbit anti-human IgE and prick tests of the skin.Immunogiobulin E antibodies were found in seven out of twenty-six infants who were suspected of suffering from milk allergy. These antibodies were found also in one out of three coeliac patients and in two out of five suffering from recurrent aspiration. Other sera were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 26 publications
1
8
2
Order By: Relevance
“…Reaction of mast cell-bound reagins with cow's milk protein antigen would then result in in creased vascular permeability and possible deposit of immune complexes inducing a lo cal inflammation in the mucosa. The noted low frequency of specific IgE antibodies in patients with acute reactions, although in agreement with the findings of Kletter et al [14], is obscure, as these patients often pre sented typical manifestations of immediate type allergy. Sampling was done immediate ly before positive provocations and, there fore, antibody consumption is no explana tion for the negative findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reaction of mast cell-bound reagins with cow's milk protein antigen would then result in in creased vascular permeability and possible deposit of immune complexes inducing a lo cal inflammation in the mucosa. The noted low frequency of specific IgE antibodies in patients with acute reactions, although in agreement with the findings of Kletter et al [14], is obscure, as these patients often pre sented typical manifestations of immediate type allergy. Sampling was done immediate ly before positive provocations and, there fore, antibody consumption is no explana tion for the negative findings.…”
Section: Discussionsupporting
confidence: 89%
“…Dif ferent serologic techniques have been ap plied extensively in clinical work, so far without facilitating the diagnosis apprecia bly [24], Usually the applied methods have quantified the levels of specific antibodies to cow's milk proteins belonging to the immu noglobulin classes IgG or IgM [6,12,19,20], while investigations of IgE and IgA an tibodies are sparse in cases of gastrointesti nal cow's milk protein intolerance [5,14]. Furthermore, it is usually not possible to es tablish, in the reports, the relation between time of sampling and exposition/elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Kletter et fl/. [1] did not detect any IgE antibodies to non-processed ^-lactoglobulin in the sera from infants below 1-year-old with suspected cow's milk allergy, while in the present study, IgE antibodies to cow's milk were found even in young infants. The findings of high levels of IgG antibodies against cow's milk proteins, especiallŷ -lactoglobulin in slowly appearing intolerance to cow's milk, suggest that these reactions to cow's milk may be mediated by immune complexes.…”
Section: Discussioncontrasting
confidence: 65%
“…However, the circulating antibodies may participate in the disposal of environmental antigens from the gastrointestinal tract. Titers of antibodies to dietary antigens appear to decline with age during childhood, except in children with altered gastrointestinal perme ability [6], A few studies on the immunoglobulin class distri bution of antibodies against dietary antigens in chil dren have been published, and IgE antibodies have been implicated in food intolerance [7][8][9][10], Several aspects of the human immune response to dietary antigens such as its relation to food allergy, the specificity and avidity of the antibodies, and their isotype and subclass distribution require further studies [ 11],…”
Section: Introductionmentioning
confidence: 99%